Residential Building Resilience Model Against Seismic Disaster with Fuzzy Logic–Fragility Analysis Approach - Setiono; Senot Sangadji; Stefanus A. Kristiawan; Nur Miladan (Civil Engineering Journal, 2026)
Residential buildings are part of the urban physical infrastructure most affected by a seismic disaster. The resilience (R) of residential buildings should be evaluated for disaster mitigation before, during, and after disasters to minimize potential damage. This study proposed an R evaluation model for residential buildings that combined a fragility analysis and a fuzzy logic approach. The developed model combined the functionality (q) and recovery time (t) to obtain the R index. A fragility analysis was used to calculate the q of residential buildings, where the t was normalized to the longest possible t (0–1) for input into the fuzzy inference process, which depended on government decisions and other factors, including the available budget and other conditions. Resilience (R) was computed using a fuzzy logic (FL) approach with the Tsukamoto inference system. The research resulted in a model for evaluating the R of residential buildings for seismic disasters. The value of the research lies in the conversion of probabilistic damage decisions into fuzzy representations of post-earthquake q and t, so that both variables can be coupled within a single decision-focused model. The model was applied to simulate the R of residential buildings in Surakarta City during an earthquake. One- and two-story buildings accounted for more than 98% of the residential building data. The R for residential buildings under the applied scenario for a spectral acceleration (Sa) of 0.16 g was quantified at 52.47%, indicating a condition of moderate resilience. The developed model can help the government to evaluate the R of residential buildings and can be adjusted for other components of urban infrastructure, such as transportation, electricity, and telecommunication networks.